Human Papillomavirus (HPV) 16 E6 seropositivity is elevated in subjects with oral HPV16 infection - Zhang, Yuehan (Cancer Epidemiol, 2016)
INTRODUCTION: Human Papillomavirus (HPV) 16 E6 serum antibodies are common in people with HPV-related oropharyngeal cancers (HPV-OPC), but not the general population. We explored HPV16 seroprevalence in people with and without oral HPV16 infection, the cause of HPV-OPC. METHODS: Oral rinse samples were collected semiannually and tested for 36 types of HPV DNA by PCR. HPV16 E6 serum antibodies were tested at the visit of first oral HPV detection in participants with prevalent (n=54), or incident (n=39) oral HPV16 DNA; or at baseline in matched participants with no oral HPV16 DNA (n=155) using multiplex serology assay. Predictors of seropositivity were examined using logistic regression. RESULTS: HPV16 E6 seropositivity (7.5% vs 0.7%; p=0.005) but not seropositivity to the other HPV16 antigens, was significantly more common in those with than without oral HPV16 infection. There were only 8 HPV16 E6 seropositive participants, but oral HPV16 DNA remained a strong predictor of E6 seropositivity after adjustment for other risk factors (aOR=14.6 95%CI, 1.7-122.5). Seroprevalence was similar in those with prevalent (7.4%; 4/54), and incident (7.7%; 3/39) oral HPV16 infection (p=1.00). E6 seroprevalence was associated with reduced oral HPV16 clearance, but was not statistically significant (HR=0.65 95% CI, 0.16-2.70). Seropositive participants were primarily male (87.5%), HIV-positive (75.0%; median CD4 cell-count of 840) and had oral HPV16 DNA (87.5%). History of an HPV-related cancer (0/8) or HPV-related anogenital dysplasia (1/8) was rare, and 4 participants had recent screening showing no anogenital dysplasia. DISCUSSION: HPV16 E6 seropositivity was higher among people with than without oral HPV16 infection, despite no known anogenital disease in these participants.